INTEGRATION OF MODERN TECHNOLOGIES INTO THE SYSTEM OF QUALITY MANAGEMENT OF EDUCATIONAL SERVICES - Makhmudalieva Mahmudakhon Jakhongir qizi (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract: In recent decades, the global education sector has undergone numerous transformations,  influenced  by  the  growing  demands  of  society  for  high-quality educational  services.  The  ever-increasing  pace  of  technological  advancement  has inevitably  impacted  educational  institutions,  prompting  a  critical  need  to  integrate modern  technologies  into  their  quality  management  systems.  Effective  quality management  in  the  sphere  of  educational  services  remains  essential  for  not  only ensuring  academic  excellence  but  also  for  enhancing  the  overall  satisfaction  of stakeholders, including students, educators, employers, and the wider community.